Impact of Teachers on an Australian Community Over Ten Years: A Qualitative Study - Derek Brawner; Carrie Ann Stephens; Shelby Brawner; Christopher T Stripling; Neal Samuel Eash (Journal of International Agricultural and Extension Education, 2016)
The purpose of this study was to use intensive interviews to evaluate the impact of American teachers on a ruralcommunity in New South Wales, Australia from 2005 to 2015. The study analyzed interviews with 10participants ofthe Australian community. Survey participants were chosen based on their longevity in the community and their community involvement. Tworesearchersand a peer reviewer transcribed, coded,and categorized the data into themessuggested by the interview participants using participatory action research. Results from this studyidentified two major themes: impact on student growth and sense of community, and eight subthemes: student performance, international growth, culture, perceptions and stereotypes, values, pre and post impressions of American teachers, involvement within the community, and community acceptance
Keywords: Community impact; cultural perceptions; stereotype